Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. Join them; it only takes a minute:

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

I know how to use the standard rule

$$p\vee (q\wedge r)\equiv (p\vee q)\wedge (p\vee r)$$

but what if I have a two by two statement like:

$$(p\vee q)\wedge (r\vee s)$$ ...

I'm guessing that it follows a similar rule to the FOIL method in algebra? I took a shot in the dark and came up with this, but I want to make sure my logic is correct.

$$(p\wedge r)\vee (p\wedge s)\vee (q\wedge r)\vee (q\wedge s)$$

share|cite|improve this question
What you wrote is correct.I just don't understand why you're not sure about what you wrote. Notice that, por instance, $p\vee q$ is a statement itself, so you can apply the rule just as you did. – Git Gud Jan 17 '13 at 17:25
up vote 1 down vote accepted

You’re right: the underlying law is the same as in ordinary algebra, so the calculation works out in the same fashion. In detail:

Think of $p\lor q$ as a single entity; call it $t$ temporarily. Then you have

$$t\land(r\lor s)\equiv(t\land r)\lor(t\land s)\;.$$

Now expand $t$ in each of the disjuncts:

$$t\land r\equiv(p\lor q)\land r\equiv(p\land r)\lor(q\land r)$$


$$t\land s\equiv(p\lor q)\land s\equiv(p\land s)\lor(q\land s)\;,$$

so the original expression is equivalent to

$$\Big((p\land r)\lor(q\land r)\Big)\lor\Big((p\land s)\lor(q\land s)\Big)\;.$$

Finally, the big parentheses are clearly unnecessary, so you have

$$(p\land r)\lor(q\land r)\lor(p\land s)\lor(q\land s)\;.$$

share|cite|improve this answer

Let $t=p\lor q$. Then:

$$(p\lor q) \land (r\lor s) = t\land (r\lor s) = (t\land r)\lor(t\land s)$$

Substitute back $p\lor q$ and you get:

$$=((p\lor q)\land r)\lor ((p\lor q)\land s)$$

Now distribute the sub-expressions:

$$(p\lor q)\land r) = (p\land r)\lor (q\land r)$$ $$(p\lor q)\land s) = (p\land s)\lor (q\land s)$$

Substituting back in you get:

$$\begin{align}(p\lor q) \land (r\lor s) &= ((p\land r)\lor (q\land r))\lor ((p\land s)\lor (q\land s))\\ &= (p\land r)\lor (q\land r)\lor (p\land s)\lor (q\land s) \end{align}$$

share|cite|improve this answer

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.